تطبيقات الذكاء الاصطناعي: كتوجه حديث لمواجهة تداعيات وباء كورونا المستجدة - هدار رانية (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
شكل ظهور وباء كورونا جائحة عالمية خطيرة أثرت على مجريات الصحة العالمية بشكل غير مسبوق، مما فرض على الدول اتخاذ تدابير وقائية صارمة حفاظا على الصحة العامة، والتي خلفت تداعيات خطيرة تجاوزت البعد الصحي لتطال أغلب المجالات الحياتية. ومن ثما، فإن هذه الدراسة تهدف إلى معرفة كيف أسهم الذكاء الاصطناعي وتطبيقاته المختلفة كتوجه حديث في الاستجابة لتداعيات الوباء والدور الذي لعبته في مواجهة آثاره السلبية. وقد أظهرت نتائج الدراسة أن تطبيقات الذكاء الاصطناعي شكلت خيار طارئ لعب دورا حيويا مزدوجا في احتواء تداعيات الأزمة وتحجيم آثارها السلبية، وذلك من خلال ما قدمته من أفكار إبداعية وحلول ابتكارية أسهمت في السيطرة على انتشار الوباء وسد الفجوة التي سببتها المشاكل المصاحبة له صحيا وخدماتيا والتي ساعدت على تجاوز فترة الإغلاق والحجر بفعالية. The emergence of the Corona virus caused a serious global pandemic that affected the course of the world health in an unprecedented way, forcing countries to take strict preventive measures to preserve public health, which had serious repercussions that went beyond the health dimension to affect most areas of life. Hence, this study aims to find out how artificial intelligence and its various applications, as a modern trend, contributed to responding to the repercussions of the epidemic and the role it played in confronting its negative effects. The results of the study showed that the applications of artificial intelligence constituted an emergency option that played a double vital role in containing the repercussions of the crisis and limiting its negative effects, through the creative ideas and innovative solutions it presented that contributed to controlling the spread of the epidemic and bridging the gap caused by the accompanying problems. It has health and services that helped to effectively bypass the period of closure and quarantine